Nursing theorists and their work - Alligood, Martha Raile; Marriner-Tomey, Ann , 1943- (Mosby/Elsevier, 2010)
Offers a look at 49 theorists of historical, international, and significant importance. This book includes case studies and critical thinking activities that help bridge the gap between theory and application